Estimating degradation of strength of neat PEEK and PEEK-CF laminates under cyclic loading by mechanical hysteresis loops - Alexey Bogdanov; Alexander Eremin; Mikhail Burkov; Sergey Panin; Pavel Lyubutin (Fracture and Structural Integrity)
A DIC-based method was employed for assessing the fatigue induced degradation of mechanical properties of neat polyetheretherketone (PEEK) and its laminated composite reinforced with unidirectional carbon fibers. Its operation principle is based on the remote measurement and calculation of the maximum and minimum strains in a cycle, as well as both dynamic and secant moduli estimated from mechanical hysteresis loops. It is shown that these parameters reflect the degree of material damaging, enabling to predict its current mechanical state.